GAMBITS : CONVERSATIONAL STRATEGY SIGNALS USED BY NON-NATIVE SPEAKERS OF ENGLISH IN NATURAL CONVERSATION - A. Soerjowardhana (Fakultas Ilmu Budaya, Universitas Dian Nuswantoro, 2015)
A verbal spoken communication (conversation) is considered successful when the speaker and listener can understand each other. Unlike children who easily master their native language, adult foreign language learners, although they have learned and practiced the foreign language for years, are in general not able to use thelanguage even for basic communication purposes. To get the success of a conversation people can use gambits (words and phrases that serve regulate the smooth flow of a conversational talk). Although gambits do not have meaning in the traditional sense of the words, they are a very important part of conversational behavior.In this study the data were obtained from a conversation between an Indonesian girl and a Dutch man who was staying in Indonesia for a visit. TheIndonesian girl had an assignment to interview a foreigner who was staying in Indonesia. The interviewer’s English is in intermediate level. The finding shows that the four main functions of gambits are demonstrated in the conversation, consisting mainly state consciousness signal which is demonstrated twelve times, semanticframing (eight times), communication control signals (six times), and the last signaling of social context (twice).Key words: conversational strategy signals, state consciousness signal, semantic framing, communication control signals, signaling of social context